Cryopreservation of canine spermatozoa using a skim milk‐based extender and a short equilibration time. Issue 11 (6th September 2020) - Abe, Yasuyuki; Asano, Tomoyoshi; Wakasa, Ichiko; Kume, Aiko; Yokozawa, Sakimi; Umemiya‐Shirafuji, Rika; Suzuki, Hiroshi
Abstract: Although useful spermatozoa cryopreservation techniques have been established, long‐term equilibration seems to be required before freezing the spermatozoa of many species, including dogs. The fertility of cryopreserved dog spermatozoa from five males for a reduced equilibration period (0, 30, 60, 120 and 180 min) in a skim milk (SM)‐based extender containing raffinose was evaluated in the present study. When the sperm was diluted with the extender at room temperature (RT) and cryopreserved without equilibration, the proportion of total motile spermatozoa (TMS) after thawing was lower (27%) than when the sperm was equilibrated for 30 min (33%), 60 min (32%), 120 min (44%; p  < .05) or 180 min (29%). The proportion of TMS increased as the equilibration time increased and peaked at 120 min. Acrosome integrity was significantly lower in the cryopreserved spermatozoa that had not undergone the initial equilibration than in the equilibrated spermatozoa ( p  < .05). The normal rate of acrosomes increased with the extension of the first equilibration and peaked at 120 min. When frozen–thawed spermatozoa that had been diluted at RT and subjected to an initial equilibration lasting 60 or 180 min were transcervically inseminated into recipients, there were no differences in the delivery rate, litter size or breeding efficiency. In the cryopreservation of canine spermatozoa using a SM‐based extender, even if the initial equilibration time was shortened to 60 min, the results were comparable to those obtained when the conventional method (with an initial equilibration time of 180 min) was used.